Penerapan Metode Muhadatsah dalam Meningkatkan Maharah Kalam Siswa MTs Al Irsyad Tengaran - Khamdani, Agus Walid; Subando, Joko (TSAQOFAH, 2026)
Arabic language learning at madrasah tsanawiyah continues to face obstacles in developing students’ speaking skills (maharah kalam), particularly with regard to fluency, pronunciation accuracy, and willingness to speak, which are partly caused by grammar-oriented teaching and limited oral communication practice. This study aimed to analyze the implementation of the muhadatsah method in improving maharah kalam among students at the madrasah tsanawiyah level. The research employed a qualitative approach with a descriptive design and was conducted at MTs Al-Irsyad Tengaran. Data were collected through classroom observations, in-depth interviews with Arabic language teachers and students, and documentation, and were analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. The findings showed that the implementation of the muhadatsah method improved students’ participation, speaking fluency, pronunciation accuracy, and self-confidence in communicating in Arabic. The study concludes that the muhadatsah method is an effective communicative learning approach for enhancing students’ maharah kalam and is relevant for application in Arabic language learning at madrasah tsanawiyah, thus serving as a pedagogical strategy to continuously strengthen students’ speaking competence.